Greek astronomy - Heath, Thomas Little 1861-1940 (Cambridge University Press, 2014)
From its beginnings in Babylonian and Egyptian theories, through its flowering into revolutionary ideas such as heliocentricity, astronomy proved a source of constant fascination for the philosophers of antiquity. In ancient Greece, the earliest written evidence of astronomical knowledge appeared in the poems of Homer and Hesiod. In the present work, first published in 1932, Sir Thomas Little Heath (1861-1940) collects some of the most notable essays and discussions of astronomical theory by Greek astronomers and mathematicians, presenting them in English translation for the modern reader. With chronological coverage, Heath's book features a thorough introduction, a doxography of what ancient authors said about the earliest theorists and longer excerpts exploring fundamental ideas. Among the pieces are extracts from Plato's Republic and Ptolemy's work on the impossibility of a moving Earth, alongside material from Aristotle, Euclid, Strabo, Plutarch and others.